Ovarian Carcinoid: a Rare Experience - Malla, Maryada; Marahatta, R; Shrestha, A; Pudasaini, S (Nepal Medical College Journal, 2019)
Carcinoid tumors are neuroendocrine tumors. They occasionally secrete serotonin and associated factors that result in a unique constellation of features termed carcinoid syndrome. We report a case of primary ovarian carcinoid, which is a rare condition. A 54 year old lady presented at Obstetric Gynecology Depatment of NMCTH with history of gradually increasing mass in lower abdomen for 3 years. She also had intermittent flushing of face, sweating, shortness of breath, and multiple episodes of loose stools. Examination revealed a mobile mass felt separate from the uterus. Ultrasound, tumor markers and CT scan abdomen were performed. She then underwent staging laparotomy. Histopathology and immunohistochemistry were suggestive of neuroendocrine tumor. HAfter surgery her symptoms disappeared and she was discharged on the 4th postoperative day.